A Phase II Toxicity End Point Trial (ICORG 99-09) of Accelerated Dose-escalated Hypofractionated Radiation in Non-small Cell Lung Cancer. Issue 1 (January 2018) - Cagney, D.N.; Thirion, P.G.; Dunne, M.T.; Fleming, C.; Fitzpatrick, D.; O'Shea, C.M.; Finn, M.A.; O'Sullivan, S.; Booth, C.; Collins, C.D.; Buckney, S.J.; Shannon, A.; et al.
Abstract: Aims: The objective of this phase II clinical trial was to prospectively evaluate the safety and efficacy of accelerated hypofractionated three-dimensional conformal radiation therapy (3DCRT) in localised non-resectable/non-operable non-small cell lung cancer (NSCLC). Materials and methods: Sixty patients with stage I–III NSCLC were enrolled in a prospective single-arm All Ireland Co-operative Oncology Research Group (ICORG 99-09) toxicity end point phase II trial. The protocol allocated patients between three radiation schedule dose levels (60, 66 or 72 Gy, in 20, 22 and 24 fractions, respectively, 3 Gy daily, five fractions per week) according to combined lung V25Gy (V25Gy  ≤ 30%) with built-in early stopping toxicity rules. The primary end point was toxicity with evaluation of dose-limiting toxicity. The secondary objectives included radiological tumour response rate at 3 months after the completion of radiation therapy and the thoracic progression-free survival time. Results: Sixty patients were recruited from August 1999 to June 2009. Forty-nine patients were included in the primary per-protocol analysis. Eleven patients were not evaluable. In the first 30 evaluable patient cohort, severe oesophageal toxicity was reported in two patients (2/49; 4% experiencing grade 5 oesophageal late toxicity, related to the 97% oesophageal length). The trial was temporarily closed and was then reopened to validate an oesophageal dose volume constraint (DVC) of limiting the length of oesophagus fully encompassed by the 97% isodose to less than 1 cm (applied to 21 patients). The trial prospectively showed the safety of the oesophageal DVC, with no oesophageal toxicity above grade 3 thereafter. Thirty-nine per cent of patients had disease progression at 3–4 months after radiotherapy, 22% had stable disease, 20% had a complete response and 14% had a partial response. The median overall survival was 13.6 months (95% confidence interval 10.5–16.7) and overall survival at 1 and 3 years was 57% and 29%, respectively. Conclusion: A strategy using accelerated hypofractionated 3DCRT is feasible and reasonably safe for patients with inoperable NSCLC. It is safe to deliver for centrally located tumours if DVCs are applied to the oesophagus, which is the primary dose-limiting toxicity. Further studies are required to assess the efficacy of hypofractionated regimens for centrally located tumours using an oesophageal DVC and monitoring for oesophageal toxicity. Highlights: A hypofractionated accelerated course of radiation is feasible and reasonably safe in patients with inoperable non-small cell lung cancer. Care must be given to limit the length of the oesophagus in the high dose region. Further studies to evaluate oesophageal dose volume constraint is warranted.